2016
DOI: 10.18632/aging.100924
|View full text |Cite
|
Sign up to set email alerts
|

Lack of collagen VI promotes neurodegeneration by impairing autophagy and inducing apoptosis during aging

Abstract: Collagen VI is an extracellular matrix (ECM) protein with a broad distribution in different tissues and mostly deposited at the close periphery of the cell surface. Previous studies revealed that collagen VI protects neurons from the toxicity of amyloid-βpeptides and from UV-induced damage. However, the physiological role of this protein in the central nervous system (CNS) remains unknown. Here, we established primary neural cultures from murine cortex and hippocampus, and carried out in vitro and in vivo stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 69 publications
(92 reference statements)
2
49
0
1
Order By: Relevance
“…Recent work by our group, aimed at investigating the physiological role for ColVI in the brain, also reported ColVI expression in primary hippocampal neurons, as well as in the meninges and brain blood vessels, in the hippocampal region, and in the corpus callosum ( Box 1 ). Moreover, we demonstrated the presence of distinctive neurodegenerative traits in aged ColVI knockout ( Col6a1 −/− ) mice ( Box 2 ), pointing at a protective role for ColVI in physiological aging ( Cescon et al, 2016 ), further corroborating the concept that ColVI protects neuronal cells against age-dependent neurodegeneration. Using wild-type and Col6a1 −/− mice, we found that the COL6 genes were upregulated during aging and demonstrated that geriatric (23-month-old) ColVI-null mice displayed a higher incidence of apoptosis, higher oxidative damage and altered autophagic flux in neuronal cells compared with age-matched wild-type mice.…”
Section: Colvi In the Cnssupporting
confidence: 70%
See 2 more Smart Citations
“…Recent work by our group, aimed at investigating the physiological role for ColVI in the brain, also reported ColVI expression in primary hippocampal neurons, as well as in the meninges and brain blood vessels, in the hippocampal region, and in the corpus callosum ( Box 1 ). Moreover, we demonstrated the presence of distinctive neurodegenerative traits in aged ColVI knockout ( Col6a1 −/− ) mice ( Box 2 ), pointing at a protective role for ColVI in physiological aging ( Cescon et al, 2016 ), further corroborating the concept that ColVI protects neuronal cells against age-dependent neurodegeneration. Using wild-type and Col6a1 −/− mice, we found that the COL6 genes were upregulated during aging and demonstrated that geriatric (23-month-old) ColVI-null mice displayed a higher incidence of apoptosis, higher oxidative damage and altered autophagic flux in neuronal cells compared with age-matched wild-type mice.…”
Section: Colvi In the Cnssupporting
confidence: 70%
“…The Col6a1 −/− mouse model bears a targeted inactivation of the Col6a1 gene, thus preventing ColVI assembly and deposition within the ECM ( Bonaldo et al, 1998 ). The use of Col6a1 −/− mice unveiled novel aspects of ColVI biology in the CNS and PNS, as discussed in the main text ( Cheng et al, 2009 ; Chen et al, 2014 , 2015 ; Cescon et al, 2016 ). Other mouse models for ColVI-related myopathies were generated, such as those targeting the Col6a3 gene.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…In a separate study the loss of miR-29a was correlated with increased levels of BACE1 and amyloid-β in sporadic Alzheimer's Disease [27]. Finally, lack of collagen VI has been related to neurodegeneration in mice models [11], and its presence has been related to a neuroprotective role against β-Amyloid toxicity [13].…”
Section: Collagen Genes Are Upregulated In Msamentioning
confidence: 92%
“…However, Col6a1 À/À mice do not show signs of increased inflammation, and appear to have a normal lifespan relative to wildtype mice, indicating that the condition in these mice may not be progressive and degenerative, but may be more likely a result of developmental defects. 55,56 It is possible that COL6 plays a role in chronic lung disease due to prematurity, as longitudinal cohort studies have shown early evidence of obstructive lung disease persisting into adolescence and young adulthood. 57,58 Genes with reduced expression in Col6a1 À/À lungs are significantly enriched with markers of endothelial cells, B Figure 5 Alveolar vasculature and epithelial type II (ATII) cells are reduced in Col6a1 À/À Lungs.…”
Section: Discussionmentioning
confidence: 99%